Barium Siloxides and Catalysed Formation of Si−O−Si' Motifs. Issue 59 (24th September 2019) - Le Coz, Erwann; Kahlal, Samia; Saillard, Jean‐Yves; Roisnel, Thierry; Dorcet, Vincent; Carpentier, Jean‐François; Sarazin, Yann
Abstract: The first unsupported barium siloxide, the homoleptic dimer [Ba2 {μ2 ‐OSi(SiMe3 )3 }3 {OSi(SiMe3 )3 }], is presented, and its structural features are discussed in the light of DFT computations. This complex, together with the related [Ba{μ2 ‐OSi(SiMe3 )3 }{N(SiMe3 )2 }]2 and their parent [Ba{N(SiMe3 )2 }2 ]2, mediates the formation of asymmetric siloxanes R3 Si−O−SiR′3 through the first case of main group metal‐mediated dehydrocoupling of silanols and hydrosilanes. Early kinetic analysis highlights an unusual catalytic manifold. Abstract : The first !! Unsupported barium siloxides have been structurally characterised for the first time. They act as effective molecular catalysts for the dehydrocoupling of hydrosilanes with silanols to generate asymmetric siloxanes R3 Si−O−SiR′3 .